Medicinal plants used in the traditional management of dog bites by herbalists in Eastern, Western, and Central Uganda - Mukasa, Paul; Ogwang, Patrick Engeu; Owor, Richard Oriko; Lejju, Julius Bunny; Olet, Eunice Apio; Gumisiriza, Hannington; Adaku, Christopher (Ethnobotany Research and Applications, 2023)
Background: Dog bites arise due to man’s casual and tactical association with dogs, and it is a global health challenge. Rural and semi-urban communities are the most affected since accessing conventional post-exposure prophylaxis is nearly a myth. As an alternative, readily available and affordable medicinal plants are used. Indigenous knowledge about such plants is limited to specialized herbalists, and with the continuous modernization of African societies, loss of such knowledge is anticipated if not documented. Therefore, the medicinal plants used to manage dog bites in Eastern, Western, and Central Uganda were documented. Methods: Snowball sampling was used to identify the specialized herbalists. An interview guide was used to collect ethnobotanical data from June 2021 to December 2022. The information collected included; names of plants used, plant parts, methods of preparation, and mode of administration. Descriptive data was analyzed using the relative frequency of citation (RFC) index and informant consensus factor (FIC). Results: A total of 31 medicinal plants, belonging to 20 families and 30 genera were documented, with the majority from family Solanaceae. The most commonly used plants were: Baccharoides lasiopus (O.Hoffm.) H.Rob., Gymnanthemum thomsonianum (Oliv. & Hiern ex Oliv.) H.Rob., Rhoicissus tridentata (L.f.) Wild & R.B.Drumm, Phytolacca dodecandra L'Her., and Nicotiana tabacum L. Leaves were the most used plant parts. The main mode of preparation was infusion. Oral and topical were the major modes of administration. Herbs obtained from the wild were the most used and the conservation strategy was planting around home compounds and in gardens. RFC was ≤ 0.27, and FIC was ≤ 0.19. Conclusion: Specialized herbalists possess vast indigenous knowledge on the utilization of medicinal plants to manage dog bites in Uganda. However, there is a need for scientific justification of the traditional therapeutic claim, in a bid to find novel bioactive compounds which can act as drug leads for the development of drugs for the treatment of dog bite-related infections.
Keywords: Dog bites; Medicinal plants; Traditional management; Uganda